Sistem Pembayaran Jasa Labuh Tambat Kapal Melalui Sistem B-Sims Oleh PT. Div Samudera Abadi Di Pelabuhan Batam - Marsya Sofiana PR. Angin; Syarifur Ridho; Taruna Ginting (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This research aims to thoroughly examine the implementation of the Batam-Seaport Information Management Sistem (B-SIMS) for the payment of berthing and mooring services carried out by PT. Div Samudera Abadi at Batam Port. The background of the problem includes the government's post-COVID-19 pandemic drive to accelerate the digital transformation of public services, particularly in ports, to enhance efficiency and transparency. The B-SIMS system, developed by the internal team of the Directorate of the Port Business Entity (BUP) of BP Batam, is designed as a digital solution to replace the previously manual, queue-based process for berthing and mooring fee payments. As a ship agent, PT. Div Samudera Abadi is responsible for reporting all ship activities, managing necessary documents, and settling port service payments. The research method employed involves a qualitative and descriptive approach. The findings show that the implementation of B-SIMS has successfully transformed the business process. Ship agents can now submit applications, monitor status, and make payments digitally through the B-SIMS sistem. This transformation significantly contributes to increased port operational efficiency, administrative transparency, and reduced physical contact, aligning with the vision for digitalizing public services in Batam. However, challenges related to sistem adaptation and early stability may still arise.